ChemInform Abstract: General and Practical Formation of Thiocyanates from Thiols. Issue 26 (June 2015) - Frei, Reto; Courant, Thibaut; Wodrich, Matthew D.; Waser, Jerome
Abstract A new method for the cyanation of thiols (I), (VI), and disulfides (IX) using cyanobenziodoxol(on)e hypervalent iodine reagents, such as (II) and (VII) is described.